General Biology - Doerder, Paul; Gibson, Ralph (Open textbook library., 2015)
The word biology means, "the science of life", from the Greek bios, life, and logos, wordor knowledge. Therefore, Biology is the science of Living Things. That is why Biology issometimes known as Life Science.